An experimental and exergy analysis of a thermal performance of a counter flow Ranque-Hilsch vortex tube with different nozzle materials - Kırmacı, Volkan; Kaya, Hüseyin; Cebeci, Ismail; Kırmacı, Volkan; Kaya, Hüseyin (Elsevier Sci Ltd, 2018)
In this study an experimental analysis was carried out about a counter flow RanqueHilsch vortex tube with different nozzle materials. In order to observe the influences of working fluids on vortex tube, thermal performance oxygen and air were used as working fluids for different inlet pressure. Fiberglass, aluminum and steel were used as nozzle materials. The main object of this study is to investigate thermal effect of nozzle materials and working fluids on thermal performance of the vortex tube. Experimental studies were made by using three different nozzle materials (fiberglass, aluminum and steel) with inlet pressure between 150 kPa to 700 kPa with arrange of 50 kPa increment. The fraction of cold mass was kept at 0.36 and the ratio of vortex tube (L/ D) was taken 10. Also an exergy analysis was carried out for each case. This study revealed that steel as a nozzle material has the highest value of temperature gradient for air as a working fluid. (C) 2017 Elsevier Ltd and IIR. All rights reserved.
Keywords: Ranque-Hilsch Vortex Tube; Refrigeration; Exergy Analysis